BIOREMEDIASI TANAH TERCEMAR LOGAM BERAT Cd, Cu, DAN Pb DENGAN MENGGUNAKAN ENDOMIKORIZA - Riri Rizki Chairiyah; Hardy Guchi; Abdul Rauf (Universitas Sumatera Utara, 2013)
The objective of this research was to study the influence of endomycorrhizae on bioremediationheavy metals of Cd, Cu, and Pb. The research was conducted from April 2012 until February 2013used non factorial randomized block design with 5 replications and 5 treatments. Applications ofheavy metals treatments are: Control (non-application of endomycorrhizae and heavy metals), L0(application of endomycorrhizae and non-application of heavy metals), L1 (application ofendomycorrhizae and heavy metals Cd 1,5 ppm, Cu 20 ppm, and Pb 60 ppm), L2 (application ofendomycorrhizae and heavy metals Cd 2,25 ppm, Cu 25 ppm, and Pb 200 ppm), and L3 (applicationof endomycorrhizae and heavy metals Cd 3 ppm, Cu 30 ppm, and Pb 340 ppm). Heavy metals wereapplied 3 weeks before planted and endomycorrhizae was applied when planting. The plants keptuntil vegatative phase in the screen house.The result of this research showed that the application of endomycorrhizae decreased Cu and Pbavailablity in soil. In the plants, application of mycorrhizae decreased Pb uptake. Applications ofendomycorrhizae and heavy metals increasing mycorrhizae infection rates, but has no effect toheavy metals uptake, shoot dry weights, root dry weights, and pH H2O soil. Heavy metalsavailability in soil only significant to Pb availability after heavy metals applications.